Development of co-disposal methods for coal discards and fine waste for the prevention of acid mine drainage - Mjonono, Donald (Centre for Bioprocess Engineering Research, 2022)
The dependence on coal ores for energy supply has led to the considerable increase in coal discards (CD) and fine waste (FW) arising from mining and processing operations. These wastes typically contain sulphide minerals, which when oxidised may lead to the generation of acidic and toxic discharge. A deficit of naturally occurring neutralising minerals to counteract this acidic discharge results in acid rock drainage (ARD). Far reaching consequences on water systems, vegetation, people and wildlife ensue as a result. To minimise the environmental burden, the acidic water resulting from the oxidation of sulphide minerals present in wastes from both active and abandoned mines is often treated with alkaline materials and is further processed to remove metals. Indefinite maintenance and operational activities emanate from these treatment processes. Further, accumulating sludge from processing streams presents post-closure liabilities. To reduce the environmental footprint, mine waste management strategies have been developed to minimise the risk of ARD formation and proliferation. In this study, the co-disposal of CD and FW was investigated as a means to prevent the initiation of oxidation reactions at source. The CD fraction is sulphide rich with high acid producing potential but can be effectively utilised to construct structurally stable beds. In these beds, large voids are formed between the particles that facilitate the transport of oxygen and water to the sulphide mineral surfaces. Co-packing FW with sulphide-rich CD provides a sustainable approach to ARD prevention. The FW has a high-water retention capacity and can be used to encapsulate, seal or cap the sulphide bearing mineral surfaces. Apart from providing a physical barrier and decreasing voids, FW typically have low sulphide content and high specific surface area that result in increased release rates of any acid neutralising minerals present in these waste materials. Co-disposal techniques thereby provide a longterm end-of-pipe approach to ARD mitigation that may offset indefinite, resource intensive, treatment options. The co-disposal of CD with FW, however, is challenging particularly at large bed cross-sectional areas, as the incidence of high percolation rates increases. This is attributed to decreased inter-particle contact that emerge in packed beds with high void ratios, decreased packing density and increased susceptibility to deformation. This undesirable packing behaviour impacts negatively on bed stability culminating in particle displacement and increased likelihood for sulphide mineral oxidation. Fine wastes conceal these sulphide minerals by either filling voids between coarse particles or forming covers with capillary barriers and acid-neutralising effects. Consequently, the generation of ARD is inhibited. At increased scale, however, the ARD prevention efficiency of covers is enhanced by increasing the CD to FW proportion to result in a structure with high load and acid buffering capacity. The approach adopted in this study entails developing packing arrangements of co-mingled CD and FW in dry-mass ratios of 3:2 and 2:3, respectively, to improve bed stability and hence prevent ARD formation with scale up. In addition to mixture ratios, improved co-packing of CD and FW is contingent on the material geochemical properties and geotechnical parameters of the resulting packed structure. As such, geochemical analyses were performed to determine the acid producing and neutralising potential of the CD and FW through acid base accounting, net acid generating and biokinetic tests followed by geotechnical assessments. The static test results indicated that the high sulphur CD (2.16% S) was potentially acid forming and the low-sulphur FW (0.84% S) was non-acid forming with high acid neutralising capacity. The co-mingled CD and FW samples (ca. 1.5% S) were deemed uncertain as the net acid producing potential was near zero and the NAG pH was less than 4.5. Accordingly, biokinetic tests were conducted over 120 days to fully understand the acid generating and neutralising rates of the inoculated and uninoculated co-mingled samples. Near-neutral conditions were sustained for prolonged periods (> 90 days) in FW dominant samples (2CD:3FW) after which a transition to acidic conditions ensued. This highlighted the limited role of acid neutralising minerals in sustaining near neutral conditions. As ARD mitigation is contingent on preventing the rapid percolation of water and exclusion of oxygen from sulphide mineral surfaces, means to prevent the rapid depletion of neutralising minerals by either dilution or washout are essential in flow through systems. This can be achieved by decreasing voids to result in increased packing density and improved bed stability. Bed stability was shown to be dependent on several interrelated factors that included the degree of saturation of the particles (water to solid ratio, W/S), CD to FW ratio, packing configuration (layers or blends), and the extent of material compaction (assisted versus unassisted packing approach). These factors were integrated to produce 16 packing arrangements. The efficiency of these configurations was compared using packing density, slump and compressibility tests. Packing densities of ca. 0.8 m3solids. m-3mould coupled with low slump spread values (< 0.391 m) were obtained for wet, unassisted packings of CD-dominant layered and blended arrangements. Comparable packing densities and slump results were obtained for assisted packings of CD-dominant layered and blend configurations under dry conditions. Dry assisted packings of either CD or FW dominant layered systems resulted in ore beds with low compressive strain (< 7%), while in wetted structures, extensions of up to 30% over extended periods (>600 s) were noted. The large compressive extensions and the delay to achieving maximum compressive strains signalled the low particle consolidation and decreased bed stability of unassisted wet packings. As engineered co-disposal approaches are associated with long-term bed stability and hence prolonged ARD prevention, select packings were further analysed to validate their efficacy using kinetic column tests of increasing scale. An acidic feed of pH 2 was continuously introduced to the test columns at a flow rate of 3.5 L.m-2.h-1 to expedite the oxidation process and to assess the efficiency of the packing arrangements for ARD mitigation. Segregated disposal of CD in small scale columns (D = 0.19 m, H/D = 1.12) with inherent large voids allowed unrestricted access of the aqueous oxidants to the exposed sulphide minerals leading to rapid discharge of highly acidic effluent (ca. pH 2). For the wet, unassisted co-packed systems, structural instability was observed with the wash out of FW and subsequent fast effluent discharge rates. With the loss of the neutralising and reactive barrier due to migration, acidic conditions presented earlier in these wet packed beds (after 30 days) than in dry packed beds (after 90 days). The loss in geotechnical stability was more prevalent in blended systems than in layered configurations, with a rapid loss of geochemical stability following soon thereafter, despite similar neutralising characteristics in both packing configurations. In these blended arrangements, non-functional migration of the fine waste particles transpired to result in unhindered access of the oxidants with the acid generating minerals. With dilution and wash out of the neutralising components, acidic reactions dominated. In multi-layered systems, a cascading effect prevailed despite breakthrough in some layers such that a fail-safe condition resulted. Consequently, near-neutral effluent discharge at low flow rates transpired. This further emphasised the importance in preventing the displacement of particles to maintain bed stability in co-disposal prevention strategies. Assisted dry packings of blends and layers were anticipated to result in improved bed stability at large scale. As such, CD dominant blends (3CD:2FW) and FW dominant blend and layered (2CD:3FW) systems were investigated in large scale columns (D = 0.32 m, H/D = 1.12). These columns were similarly exposed to aggressive leach conditions over 120 days. As with the smaller scale columns, the packing efficiency in multi-layered arrangements were higher than for the blends. In the blended systems, evolving geochemical and geotechnical conditions were similar regardless of the CD:FW ratio demonstrating the complexity in achieving homogenously packed matrices at large scale. In multi-layered configuration, bed structural stability was sustained for extended periods as the stress imposed on the packed bed was uniformly distributed across the moisture retaining FW layers and dissipated within the matrix. Correspondingly, particle displacement was minimised, and with the cascading phenomena, ARD was successfully prevented over extended periods. A dry cover system composed of multi-layers of CD and FW is therefore recommended for pilot scale studies. Dry cover systems can be easily constructed and present a cost-effective approach to sustainable mine waste management. Further evaluation of the structural stability of multi-layers at large scale is required as changes in bed geometry, particle size and environmental conditions can alter the dump geotechnical properties and hence geochemical stability.